2022
DOI: 10.3389/fnins.2022.967491
|View full text |Cite
|
Sign up to set email alerts
|

Effects of central nervous system electrical stimulation on non-neuronal cells

Abstract: Over the past few decades, much progress has been made in the clinical use of electrical stimulation of the central nervous system (CNS) to treat an ever-growing number of conditions from Parkinson’s disease (PD) to epilepsy as well as for sensory restoration and many other applications. However, little is known about the effects of microstimulation at the cellular level. Most of the existing research focuses on the effects of electrical stimulation on neurons. Other cells of the CNS such as microglia, astrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 158 publications
0
4
0
Order By: Relevance
“…Commercially available deep brain electrodes have up to 8 electrodes that each stimulate a cubic millimeter of neural tissue including thousands of neurons [16] and axons. Miniaturization of the electrodes combined with improved stimulation protocols have increased the specificity to ∼10 neurons [8]; nevertheless, electrode alignment [17], lack of cell specificity [18, 19, 20, 21], and the immune response [22] limit the feasibility of this technology for long term sensory neurorehabilitation.…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercially available deep brain electrodes have up to 8 electrodes that each stimulate a cubic millimeter of neural tissue including thousands of neurons [16] and axons. Miniaturization of the electrodes combined with improved stimulation protocols have increased the specificity to ∼10 neurons [8]; nevertheless, electrode alignment [17], lack of cell specificity [18, 19, 20, 21], and the immune response [22] limit the feasibility of this technology for long term sensory neurorehabilitation.…”
Section: Mainmentioning
confidence: 99%
“…[15].Commercially available deep brain electrodes have up to 8 electrodes that each stimulate a cubic millimeter of neural tissue including thousands of neurons [16] and axons. Miniaturization of the electrodes combined with improved stimulation protocols have increased the specificity to ∼10 neurons [8]; nevertheless, electrode alignment [17], lack of cell specificity [18,19,20,21], and the immune response [22] limit the feasibility of this technology for long term sensory neurorehabilitation.Biohybrid approaches, in which living cells integrated with stimulation electrodes are grafted into the tissue, have been proposed to overcome these challenges [23,24,25,26,27,28]. While allogeneic and xenogeneic transplantations of neurons and organoids into adult brains have functionally integrated new neurons into developed neural networks [29,30], neural implants have yet to leverage this for improving biocompatibility, cell specificity and stimulation resolution.…”
mentioning
confidence: 99%
“…Intraspinal microstimulation has been shown to restore some motor function after spinal cord injury. 471 In general, implanting electrodes in the central nervous system triggers inflammation and scarring, shielding the electrodes and affecting stimulation efficacy. Vara et al reported an electrostimulation probe based on PEDOT coating and carbon microfibers, in which electrons delivered by the carbon microfibers were converted into ions in the PEDOT stereostructure, therefore reducing hazardous reactions and increasing the safe charge injection limit.…”
Section: Drug Delivery Drug Delivery Has Always Been Amentioning
confidence: 99%
“…This device structure may provide a feasible solution for highly integrated fiber-like stimulators in the future. Intraspinal microstimulation has been shown to restore some motor function after spinal cord injury . In general, implanting electrodes in the central nervous system triggers inflammation and scarring, shielding the electrodes and affecting stimulation efficacy.…”
Section: Applications and Devicesmentioning
confidence: 99%